Pengaruh Penerapan Media Multibase Arithmetic Block Terhadap Kemampuan Representasi Matematis Siswa pada Materi Volume Balok dan Kubus - Risa Delistiani; Hani Handayani; Fajar Kusumah Solihin (Jurnal Edukasi Sebelas April, 2021)
This research is motivated by learning mathematics in the field of geometry with the volume of blocks and cubes which are considered as difficult subjects by elementary school students, resulting in low mathematical representation abilities of fifth grade students. One of the efforts that can be done to improve the ability of mathematical representation is Multibase Arithmetic Block media. This study aims to determine the effect of the application of Multibase Arithmetic Block media on the mathematical representation ability of fifth grade students in learning the material for volume of blocks and cubes at SD Negeri Babakan Bandung, Tanjungsari District, Sumedang Regency for the 2020/2021 academic year. The research method and design used was pre-experimental with a one-group pretest-posttest design for the fifth grade students of SD Negeri Babakan Bandung, totaling 10 students. The data of this study were collected through the pretest and posttest scores of mathematical representation abilities. The results of the study show that there is an effect of applying Multibase Arithmetic Block media to the ability of mathematical representation on the volume material of blocks and cubes in fifth grade students of SD Negeri Bababkan Bandung in the 2020/2021 school year. This can be seen from the average value of the initial understanding ability of students before treatment (pretest) obtained an average value of 69.6 while after treatment (posttest) of 84.8 and the results of the t-test showed tcount > ttable i.e. 10.22 > 2 ,2622.